Pesona Kopi Klotok: Peran Suasana Tradisional dan eWOM Memprediksi Intensi Berkunjung Ulang - Adhi Prakosa; Aqila Mandasari; Guruh Ghifar Zalzalah (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to examine the determinants of revisit intention and satisfaction as a mediator of revisit intention at Warung Kopi Klotok Kaliurang using the TPB and ECT theoretical frameworks. This research predicts consumer revisit intention using the variables of traditional atmosphere and eWOM, mediated by satisfaction. This type of research is quantitative with a sample of 164 respondents. The sampling technique employs non-probability sampling. A survey method was conducted to collect data using an online questionnaire. The researcher utilized Structural Equation Model (SEM) – Partial Least Square (PLS) Smart PLS 4.0 for data analysis. The results of this study demonstrate that eWOM plays a role in influencing consumers to have a revisit intention at traditional restaurants.